Novel polythiophene / polyanion compositions
The conductive polymer dispersion obtained by copolymerizing polythiophene and polyanionic can solve the gel stability problem of the antistatic coating in the presence of organic solvents, and achieve high stability and coatingability antistatic coating. In a variety of electronic applications.
Patent Information
- Application Number
- CN202380041394.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-20
- Filing Date
- 2023-05-15
- Publication Date
- 2024-12-27
AI Technical Summary
When the existing antistatic coatings are added with organic solvents, the gel stability is poor, resulting in increased viscosity or gel formation, affecting the coatingability and stability of the coating.
Using a conductive polymer dispersion obtained by copolymerizing polythiophene and polyanion, the dispersion medium is controlled to be water or water-soluble organic solvents by oxidative polymerization in an aqueous medium, and preferably a proton organic solvent such as alcohol or acid is used to adjust the polymer. particle size and structure to improve gelling stability.
It realizes the high gelling stability of the conductive polymer dispersion when adding organic solvents, improves the coating ability and stability, and is suitable for antistatic layers in various electronic applications.
Smart Images

Figure CN119213052A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to novel polythiophene / polyanion compositions and their use in various applications, such as antistatic layers. Background Art
[0002] Antistatic coatings are applied to poorly conductive surfaces, such as plastic films or paper, to reduce or prevent the buildup of static electricity. These coatings are an important component in a variety of electronic applications, as such static electricity can damage the equipment used. For example, antistatic coatings are used on antistatic packaging trays and in display applications such as liquid crystal displays (LCD) or organic light emitting diodes (OLED) to prevent static discharge.
[0003] Conductive polymers are used to prepare antistatic coatings because their conductivity and processability can be tuned for different coating techniques and substrates. Among them, poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) is commonly used, which is a conductive polymer composite that can be prepared as an aqueous dispersion and can be easily processed by conventional coating techniques.
[0004] PEDOT:PSS formulations are developed in order, for example, to optimize coating properties, enhance adhesion to substrates or improve coating stability. Organic solvents such as methanol, ethanol or isopropanol are often added. These solvents can, for example, improve the dispersibility of other components in the formulation. However, it has been observed that the addition of organic solvents to aqueous dispersions of PEDOT:PSS may reduce the gel stability of the dispersion. Viscosity increase or gel formation may severely reduce the coatability of the formulation.
[0005] Therefore, conductive polymer dispersions with high gel stability upon addition of organic solvents are crucial to allow the development of novel antistatic coating formulations.
[0006] WO2021 / 172199 (Panasonic) discloses a thiophene copolymer of 3,4-ethylenedioxythiophene (EDOT) and 3,4-dialkylthiophene. The amount of 3,4-dialkylthiophene in the copolymer is 0.005 to 13% by weight relative to the total weight of the thiophene copolymer. The thiophene copolymer is used for capacitors.
[0007] US9613757 (Eternal Materials Co Ltd) describes the copolymerization of EDOT and 3,4-dimethoxythiophene (90 / 10 ratio) in the presence of PSS. The particle size of the aqueous polymer dispersion and the surface resistivity of the coating film are disclosed. In a different patent of Eternal Materials Co Ltd, copolymers of different weight ratios were prepared in an ethanolic solution of iron (III) p-toluenesulfonate (US9036333). Both patents prepare polymer capacitors and neither describes the gelation behavior of the conductive polymer dispersion in the presence of an organic solvent.
[0008] JP2012255049 (Tosoh) discloses copolymers of EDOT and 3,4-dialkoxythiophene monomers in a molar ratio of 99.99 / 0.01 to 80 / 20. The thermal stability of the coating film was determined by measuring the surface resistance before and after a heating test. The composition was developed for overcurrent protection components. There is no mention of gel stability when an organic solvent is added. Summary of the invention
[0009] It is an object of the present invention to provide a conductive polymer dispersion having improved gel stability upon addition of an organic solvent.
[0010] The object of the invention is achieved by a dispersion as defined in claim 1 .
[0011] Further objects of the present invention will become apparent from the following description. DETAILED DESCRIPTION
[0012] definition
[0013] For example, the term "monofunctional" in a monofunctional polymerizable compound means that the polymerizable compound contains one polymerizable group.
[0014] For example, the term "difunctional" in a difunctional polymerizable compound means that the polymerizable compound contains two polymerizable groups.
[0015] For example, the term "multifunctional" in a multifunctional polymerizable compound means that the polymerizable compound contains more than two polymerizable groups.
[0016] The term "alkyl" means all possible variations for various numbers of carbon atoms in the alkyl group, i.e., methyl, ethyl; for three carbon atoms: n-propyl and isopropyl; for four carbon atoms: n-butyl, isobutyl and tert-butyl; for five carbon atoms: n-pentyl, 1,1-dimethylpropyl, 2,2-dimethylpropyl and 2-methylbutyl, etc.
[0017] Unless otherwise specified, the substituted or unsubstituted alkyl group is preferably a C1 to C6 alkyl group.
[0018] Unless otherwise specified, the substituted or unsubstituted alkenyl group is preferably a C2 to C6 alkenyl group.
[0019] Unless otherwise specified, a substituted or unsubstituted alkynyl group is preferably a C2 to C6 alkynyl group.
[0020] Unless otherwise specified, the substituted or unsubstituted alkaryl group is preferably a phenyl group or a naphthyl group including one, two, three or more C1 to C6 alkyl groups.
[0021] Unless otherwise specified, the substituted or unsubstituted aralkyl group is preferably C7 to C 20 Alkyl includes phenyl or naphthyl.
[0022] Unless otherwise specified, substituted or unsubstituted aryl is preferably phenyl or naphthyl.
[0023] Unless otherwise specified, the substituted or unsubstituted heteroaryl group is preferably a five- or six-membered ring substituted with one, two or three oxygen atoms, nitrogen atoms, sulfur atoms, selenium atoms or a combination thereof.
[0024] Unless otherwise specified, the substituted or unsubstituted alkylene group is preferably a C1 to C6 alkylene group.
[0025] The term "substituted", such as in substituted alkyl, means that the alkyl group may be substituted with atoms other than the atoms normally present in the group (i.e., carbon and hydrogen). For example, a substituted alkyl group may include a halogen atom or a thiol group. Unsubstituted alkyl groups contain only carbon and hydrogen atoms.
[0026] Unless otherwise specified, substituted alkyl, substituted alkenyl, substituted alkynyl, substituted aralkyl, substituted alkaryl, substituted aryl and substituted heteroaryl are preferably substituted with one or more members selected from the group consisting of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl and tert-butyl, esters, amides, amines, ethers, thioethers, ketones, aldehydes, sulfoxides, sulfones, sulfonates, sulfonamides, -Cl, -Br, -I, -OH, -SH, -CN and -NO2.
[0027] Conductive polymer dispersions
[0028] Dispersions comprising conductive polymers are referred to herein as conductive polymer dispersions.
[0029] The conductive dispersion according to the present invention comprises a conductive polymer and a polyanion, both of which are described below.
[0030] The dispersion medium of the conductive polymer dispersion is preferably selected from water, a water-soluble organic solvent, or a mixture thereof. The preferred organic solvent is a protic organic solvent, such as an alcohol or an acid. The dispersion medium is preferably water.
[0031] The conductive polymer dispersion may contain further ingredients, such as a dispersant.
[0032] The conductive polymer dispersion is preferably prepared as follows.
[0033] The median particle size of polythiophene / polyanion particles (d 50 ) is preferably 1 to 150 nm, more preferably 2 to 50 nm, most preferably 5 to 40 nm. 50 The particle size is preferably measured by laser diffraction.
[0034] Conductive polymers
[0035] The conductive polymer according to the present invention is an oligothiophene or polythiophene obtained by copolymerizing at least one monomer according to formula I with at least one monomer according to formula II,
[0036]
[0037] in
[0038] A represents a substituted or unsubstituted C1 to C5 alkylene bridge;
[0039] R is selected from a linear or branched substituted or unsubstituted C1-C 18 -alkyl, substituted or unsubstituted C5-C 12 -cycloalkyl, substituted or unsubstituted C6-C 14 -aryl, substituted or unsubstituted C7-C 18 - aralkyl, substituted or unsubstituted C1-C4-hydroxyalkyl and hydroxy;
[0040] s represents an integer from 0 to 8;
[0041] Ra and Rb are independently selected from hydrogen, substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted aralkyl, substituted or unsubstituted alkaryl, and substituted or unsubstituted aryl or heteroaryl;
[0042] Characterized in that the weight ratio of the monomer according to formula I to the monomer according to formula II is 75 / 25 to 25 / 75, preferably 70 / 30 to 40 / 60, more preferably 65 / 35 to 50 / 50.
[0043] Monomers according to formula I
[0044] The conductive polymer according to the present invention is an oligothiophene or polythiophene obtained by copolymerization of at least one monomer according to formula I,
[0045]
[0046] in
[0047] A represents a substituted or unsubstituted C1 to C5 alkylene bridge;
[0048] R is selected from a linear or branched substituted or unsubstituted C1-C 18 -alkyl, substituted or unsubstituted C5-C 12 -cycloalkyl, substituted or unsubstituted C6-C 14 -aryl, substituted or unsubstituted C7-C 18 - aralkyl, substituted or unsubstituted C1-C4-hydroxyalkyl and hydroxy;
[0049] s represents an integer from 0 to 8.
[0050] The term C1 to C5 alkylene bridge as used in formula I refers to an alkylene bridge containing 1 to 5 carbon atoms.
[0051] The C1 to C5 alkylene bridge is preferably methylene, ethylene, n-propylene, n-butylene or n-pentylene.
[0052] C1-C 18 -Alkyl includes straight or branched C1-C 18 Alkyl, for example methyl, ethyl, n-propyl or isopropyl, n-butyl, isobutyl, sec-butyl or tert-butyl, n-pentyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1-ethylpropyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 2,2-dimethylpropyl, n-hexyl, n-heptyl, n-octyl, 2-ethylhexyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-hexadecyl or n-octadecyl.
[0053] C5-C 12 -Cycloalkyl represents, for example, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl or cyclodecyl.
[0054] C6-C 14 -Aryl represents, for example, phenyl or naphthyl.
[0055] C7-C 18 Aralkyl represents, for example, benzyl, o-, m-, p-tolyl, 2,3-, 2,4-, 2,5-, 2,6-, 3,4-, 3,5-xylyl or mesityl.
[0056] Preferred substituents are alkyl, cycloalkyl, aryl, aralkyl, alkoxy, halogen, ether, thioether, disulfide, sulfoxide, sulfone, sulfonate, amino, aldehyde, ketone, carboxylate, carboxylic acid, carbonate, carboxylate, cyano, alkylsilane and alkoxysilane groups and carboxamide groups.
[0057] A in formula I is preferably an ethylene bridge.
[0058] In a particularly preferred embodiment, the monomer according to formula I is 3,4-ethylenedioxythiophene.
[0059] Monomer according to formula II
[0060] The conductive polymer according to the present invention is an oligothiophene or polythiophene obtained by copolymerization of at least one monomer according to formula II,
[0061]
[0062] in
[0063] Ra and Rb are independently selected from hydrogen, substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted aralkyl, substituted or unsubstituted alkaryl, and substituted or unsubstituted aryl or heteroaryl.
[0064] Ra and Rb in formula II preferably represent alkyl groups.
[0065] In a particularly preferred embodiment, the monomer according to formula II is 3,4-dimethoxythiophene.
[0066] Typical monomers according to Formula II are shown in Table 1, but are not limited thereto.
[0067] Table 1
[0068]
[0069]
[0070]
[0071]
[0072] Polyanions
[0073] The conductive polymer dispersion comprises a polymeric polyanion, wherein at least 75 mol%, more preferably at least 80 mol%, more preferably at least 90 mol%, and most preferably at least 99 mol% of the monomer units of the polyanion comprise substituents selected from sulfonic acid or salts thereof, phosphonic acid or salts thereof, phosphate or salts thereof, sulfate or salts thereof, and carboxylic acid or salts thereof.
[0074] The functional group is preferably a sulfonic acid or a salt thereof.
[0075] The polymeric polyanion may be a copolymer of different monomers, but is preferably a homopolymer.
[0076] In a particularly preferred embodiment, the polymeric polyanion is styrene-based.
[0077] According to a particularly preferred embodiment, the polyanion is poly(4-styrenesulfonic acid) or a salt thereof.
[0078] The weight average molecular weight (Mw) of the polyanion is not particularly limited, but is preferably 1,000 to 1,000,000 Da, more preferably 50,000 to 500,000 Da, and most preferably 100,000 to 300,000 Da.
[0079] Preparation of Conductive Polymers
[0080] The polythiophene polymer is preferably prepared by oxidative polymerization of the above-mentioned thiophene monomer in an aqueous medium.
[0081] The oxidative polymerization is preferably carried out in the presence of a polyanion.
[0082] The concentration of the thiophene monomer in the aqueous medium is preferably in the range of 0.1 to 25% by weight, preferably in the range of 0.5 to 10% by weight, both relative to the total weight of the aqueous reaction medium.
[0083] Suitable oxidizing agents are iron(III) salts, such as FeCl3, and iron(III) salts of aromatic and aliphatic sulfonic acids; H2O2; K2Cr2O7; KMnO4, alkali metal perborates; alkali metal persulfates or ammonium persulfates; and mixtures thereof.
[0084] Other suitable oxidizing agents are described, for example, in Handbook of Conducting Polymers (Ed. Skotheim, TA), Marcel Dekker: New York, 1986, Vol. 1, pages 46-57.
[0085] Particularly preferred oxidizing agents are peroxodisulfate salts, in particular K2S2O8, Na2S2O8; iron(III) salts, in particular iron(III) chloride; or combinations thereof.
[0086] Mixtures of peroxodisulphate and at least one further compound which catalyses the cleavage of the peroxodisulphate, for example an Fe(III) salt, are particularly preferred.
[0087] According to a particularly preferred embodiment, the oxidizing agent is a mixture of Fe2(SO4)3 and Na2S2O8.
[0088] There are different methods for preparing the aqueous reaction medium. The thiophene monomer can be dissolved or dispersed in the aqueous reaction medium and then one or more oxidants are added, which are also dissolved or dispersed in the aqueous phase, or one or more oxidants are first dissolved or dispersed in the aqueous reaction medium and then the thiophene monomer is added, which is also dissolved or dispersed in the aqueous phase.
[0089] If more than one oxidizing agent is used, for example a mixture of Fe2(SO4)3 and Na2S2O8, it is also possible to first mix one of these components with the thiophene monomer in the aqueous reaction medium and then add the second oxidizing agent.
[0090] The oxidative polymerization is preferably carried out under an inert atmosphere, as disclosed in EP-11453877 (Agfa Gevaert). When an oxidizing agent (e.g. peroxodisulfate) is added to the reaction medium, the oxygen content of the reaction medium is preferably less than 3 mg / liter, more preferably less than 1.5 mg / liter, and most preferably less than 0.5 mg / liter.
[0091] The oxygen concentration in the reaction medium can be adjusted by any means, such as freeze-thaw techniques, bubbling an inert gas such as argon, nitrogen or helium through the reaction medium for a long time, consuming oxygen in a sacrificial reaction under an inert gas blanket. Preferably, the inert gas is bubbled through the reaction medium until the polymerization is complete, thereby maintaining the oxygen concentration below 3 mg / l.
[0092] The oxidative polymerisation is preferably carried out at low pH, as disclosed in EP-A 1 384 739 (Heraeus). The pH is preferably 1.5 or lower, more preferably 1.00 or lower.
[0093] To adjust the pH, an acid may be used, preferably selected from water-soluble inorganic acids and water-soluble organic acids. Examples of inorganic acids are hydrochloric acid, sulfuric acid, nitric acid and phosphoric acid. Examples of organic acids include p-toluenesulfonic acid, benzenesulfonic acid, methanesulfonic acid and trifluoromethanesulfonic acid.
[0094] The temperature of the reaction mixture is preferably between 0 and 100°C, more preferably between 0 and 50°C, most preferably between 5 and 30°C.
[0095] The amounts of thiophene monomer and polyanion in the reaction mixture are selected to obtain a stable polythiophene / polyanion dispersion wherein the solids content is preferably from 0.05 to 25 wt%, more preferably from 0.1 to 10 wt%, and most preferably from 0.8 to 2 wt%.
[0096] After the polymerization reaction is complete, the liquid composition can be further purified, for example by filtration, in particular by ultrafiltration, and / or by treatment with ion exchangers, in particular by treatment with anion exchangers and cation exchangers.
[0097] After the purification step, the conductive polymer dispersion can be further optimized for the application it is to be used in. For example, when used to prepare an antistatic layer, the liquid formulation described below can be prepared from the conductive polymer dispersion.
[0098] Various homogenization techniques can be used in the preparation of conductive polymers. The homogenization technique can be selected from:
[0099] -Ultrasonic homogenization technology;
[0100] - Pressure homogenization technology; and
[0101] - Mechanical homogenization technology.
[0102] Preferred mechanical homogenizers are rotor-stator homogenizers and blade-type homogenizers.Another mechanical homogenization technique may be the use of a rotating disk reactor.
[0103] Preferred high pressure homogenizers, such as a Gaulin homogenizer or an Ariete homogenizer, force the dispersion under pressure through a very narrow channel or orifice. Another preferred high pressure homogenizer is a microfluidizer.
[0104] Two or more homogenizers may be used in combination, preferably in series.
[0105] Homogenization techniques can be used before, during and after polymerization. These homogenization techniques can also be used during the preparation of the liquid formulations described below.
[0106] Liquid preparations
[0107] Depending on the application in which the conductive polymer dispersion is used, additional ingredients may be added to the conductive polymer dispersion to form a liquid formulation optimized for that application.
[0108] All or part of the additional ingredients described below may also be added to the above conductive polymer dispersion.
[0109] In addition to the above-mentioned conductive polymers and polyanions, the formulations may also contain further additives, such as solvents, surface-active substances, adhesion promoters, crosslinking agents, binders, compounds that increase conductivity, compounds that improve thermal and wet stability, acidic compounds and pH-adjusting compounds.
[0110] Preferred solvents are water or water-miscible solvents or mixtures thereof. The water-miscible solvent is preferably selected from aliphatic alcohols; such as methanol, ethanol, n-propanol and isopropanol; diacetone alcohol; aliphatic ketones, such as acetone; and methyl ethyl ketone.
[0111] According to a preferred embodiment of the liquid formulation, at least 95 wt %, more preferably at least 99 wt %, most preferably at least 99.5 wt % of the total amount of solvent in the liquid formulation is water or a mixture of water and an alcohol, and the alcohol is selected from methanol, ethanol, n-propanol, isopropanol, n-butanol or a combination thereof.
[0112] The liquid preparation preferably contains 2 to 50 wt % of an organic solvent, preferably methanol, ethanol, n-propanol, isopropanol, n-butanol or a combination thereof.
[0113] The surface-active compounds may be:
[0114] - anionic surfactants, for example alkylbenzenesulfonic acids and salts, paraffinsulfonates, alcoholsulfonates, ethersulfonates, sulfosuccinates, phosphates, alkyl ether carboxylates or carboxylates;
[0115] - cationic surfactants, for example quaternary alkylammonium salts;
[0116] - nonionic surfactants, for example linear alcohol ethoxylates, oxo alcohol ethoxylates, alkylphenol ethoxylates or alkyl polyglucosides; and
[0117] - zwitterionic surfactants, for example compounds containing both a carboxylic acid group and a quaternary ammonium group, for example lauryl-N,N-(dimethylammonio)-butyrate and lauryl-N,N-(dimethyl)-glycine betaine, compounds containing both a sulfate group and a quaternary ammonium group, for example 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonate, 3-(4-tert-butyl-1-pyridinium)-1-propanesulfonate, 3-(1-pyridinium)-1-propanesulfonate and 3-(benzyl-dimethylammonio)propanesulfonate; compounds containing both a phosphate group and a quaternary ammonium group, for example hexadecylphosphocholine, compounds containing a quaternary ammonium group and an attached hydroxyl group, for example lauryldimethylamine N-oxide, and phospholipids consisting of a quaternary ammonium head coupled to two hydrophobic fatty acids via a phosphate group and glycerol.
[0118] Particularly preferred surfactants are commercially available under the trademark and of surfactant.
[0119] Preferred adhesion promoters are organofunctional silanes or their hydrolysis products, for example 3-glycidoxypropyltrialkoxysilane, 3-aminopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane or octyltriethoxysilane.
[0120] Preferred crosslinking agents are melamine compounds, blocked isocyanates, functional silanes (eg tetraethoxysilane), alkoxysilane hydrolyzates (eg tetraethoxysilane), epoxy silanes (eg 3-glycidoxypropyltrialkoxysilane).
[0121] Particularly preferred crosslinking agents are tetraalkyl orthosilicates. Preferred tetraalkyl orthosilicates are selected from tetramethyl orthosilicate, tetraethyl orthosilicate, tetrapropyl orthosilicate, tetrabutyl orthosilicate, tetrapentyl orthosilicate, orthosilicates, and at least partially hydrolyzed products of these orthosilicates, with tetraethyl orthosilicate (TEOS) being particularly preferred.
[0122] The amount of the crosslinking agent is preferably 0.01 to 15 wt %, more preferably 0.1 to 10 wt %, most preferably 1 to 5 wt %, all relative to the total weight of the liquid formulation.
[0123] Suitable binders are selected from polyvinyl alcohol, polyvinyl pyrrolidone, polyvinyl chloride, polyvinyl acetate, polyvinyl butyrate, polyacrylate, polyacrylamide, polymethacrylate, polymethacrylamide, polyacrylonitrile, styrene / acrylate, vinyl acetate / acrylate, ethylene / vinyl acetate copolymers, polybutadiene, polyisoprene, polystyrene, polyether, polyester, sulfonated polyester, polycarbonate, polyurethane, polyamide, polyimide, polysulfone, melamine-formaldehyde resin, epoxy resin, silicone resin, silane resin, cellulose or a mixture of at least two of these binders.
[0124] Other suitable adhesives are adhesives obtained by adding a crosslinking agent such as melamine compounds, blocked isocyanates or functional silanes such as 3-glycidyloxypropyltrialkoxysilane, tetraethyl orthosilicate and tetraethyl orthosilicate hydrolyzate to a crosslinkable polymer such as polyurethane, polyacrylate or polyolefin and subsequently crosslinking.
[0125] Highly preferred binders are water soluble binders such as sulfonated polyesters.
[0126] The liquid preparation preferably includes a high boiling point solvent such as propylene glycol, ethylene glycol, diethylene glycol, dimethyl sulfoxide (DMSO), methylacetamide, dimethylacetamide, dimethylformamide, N-methylpyrrolidone, N-cyclohexylpyrrolidone or a mixture of at least two of these solvents.
[0127] Adding such a high boiling point solvent to the liquid formulation in an amount of 0.1 to 10 wt %, preferably 0.5 to 5 wt %, relative to the total weight of the liquid formulation can lead to a significant increase in conductivity.
[0128] Highly preferred high boiling point solvents are selected from N-hydroxyethylpyrrolidone, DMSO, ethylene glycol and diethylene glycol.
[0129] Preferred stability-improving compounds are gallic acid or derivatives thereof, with preferred derivatives being gallic acid esters.
[0130] Particularly preferred gallic acid esters are esters of gallic acid with sugars, which are often referred to as tannins or gallotannins. Further preferred gallic acid esters are alkyl, alkenyl, cycloalkyl, cycloalkenyl and aryl esters of gallic acid, preferably those having 1 to 15 carbon atoms, preferably 1 to 6 carbon atoms in the alkyl, alkenyl, cycloalkyl, cycloalkenyl or aryl group of the esters.
[0131] Preferred derivatives of gallic acid are gallotannins, such as tannic acid, or alkyl esters of gallic acid, such as methyl gallate, ethyl gallate, propyl gallate or a mixture of at least two of these esters.
[0132] The amount of the stability-improving compound is preferably from 0.01 to 10% by weight, more preferably from 0.1 to 5% by weight, most preferably from 0.5 to 2.5% by weight, in each case based on the total weight of the liquid preparation.
[0133] The pH of liquid formulations is generally between 1.5 and 8.0.
[0134] The pH can be adjusted by adding an appropriate acid or base to the liquid formulation. Suitable acids are inorganic acids or organic acids. Examples of inorganic acids are sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, silicic acid or a combination thereof. Examples of organic acids are acetic acid, formic acid, benzoic acid, p-toluenesulfonic acid, PSS or a combination thereof. Suitable bases are inorganic bases or organic bases. Examples of inorganic bases are sodium hydroxide, potassium hydroxide, ammonium hydroxide, sodium carbonate or a combination thereof. Examples of organic bases are dimethylaminoethanol, imidazole, ammonia, alkylamine or a combination thereof.
[0135] The viscosity of the liquid preparation is preferably between 5 and 1000 mPa.s, measured by a rheometer at 20°C and 100 s -1 The shear rate is preferably between 15 and 500 mPa.s, and most preferably between 20 and 100 mPa.s.
[0136] Adjustment of viscosity can be achieved, for example, by adding appropriate rheology modifiers to the liquid formulation.
[0137] Furthermore, it is preferred that if V t0 is the viscosity of the liquid formulation at time t = 0, and if V t0+6个月 is the viscosity of the same liquid formulation after storage in a closed container at 25°C for 6 months, the change in viscosity does not exceed 20%, preferably does not exceed 10%, and more preferably does not exceed 5%, wherein the viscosity change (ΔV) is calculated as follows:
[0138] ΔV=100%x(V t0+6个月 –V t0 ) / V t0
[0139] Further, it is preferred that the conductive layer prepared with the liquid formulation is characterized by at least one of the following properties, preferably all of these properties:
[0140] - Sheet resistance in 1x10 2 Up to 1x10 10 Ω / sq range, preferably 1x10 3 Up to 1x10 9 In the range of Ω / sq;
[0141] - a transmission of at least 98%, preferably at least 98.5%, more preferably at least 99%, and most preferably at least 99.5%;
[0142] - A pencil hardness of at least 6H, preferably at least 7H, more preferably at least 8H and most preferably at least 9H.
[0143] In this context, it is particularly preferred that if SR t0 、T t0 and PH t0 are the sheet resistance, transmission and pencil hardness of a conductive layer prepared by applying a liquid formulation to a substrate at a wet film thickness of 12 mm at time point t=0 and then removing the solvent, and if SR t0+6个月 、T t0+6个月 and PH t0+6个月 The sheet resistance, transmission and pencil hardness of a conductive layer prepared by applying the same liquid formulation to a substrate at a wet film thickness of 12 mm after storage in a closed container at 25°C for 6 months and then removing the solvent, then at least one of the following properties, preferably all of these properties are met:
[0144] - The sheet resistance does not change by more than 20%, preferably does not change by more than 10%, and most preferably does not change by more than 5%, wherein the sheet resistance change (ΔSR) is calculated as follows:
[0145] ΔSR=100%x(SR t0+6个月 –SR t0 ) / SR t0
[0146] - The transmission change does not exceed 20%, preferably does not exceed 10%, and most preferably does not exceed 5%, wherein the transmission change (ΔT) is calculated as follows:
[0147] ΔT=100%x(T t0+6个月 –T t0 ) / T t0
[0148] - The pencil hardness does not vary by more than 20%, preferably by more than 10%, and most preferably by more than 5%, wherein the pencil hardness variation (ΔPH) is calculated as follows:
[0149] ΔPH=100%x(PH t0+6个月 –PH t0 ) / PH t0
[0150] The solids content of the liquid preparations is preferably from 0.01 to 20% by weight, more preferably from 0.1 to 15% by weight, most preferably from 0.25 to 10% by weight, in each case based on the total weight of the preparation.
[0151] Layered
[0152] The layered body according to the present invention comprises a conductive layer provided on a substrate, the conductive layer comprising:
[0153] (a) at least one oligothiophene or polythiophene obtained by copolymerization of at least one monomer according to formula I and at least one monomer according to formula II,
[0154]
[0155] in
[0156] A represents a substituted or unsubstituted C1 to C5 alkylene bridge;
[0157] R is selected from a linear or branched substituted or unsubstituted C1-C 18 -alkyl, substituted or unsubstituted C5-C 12 -cycloalkyl, substituted or unsubstituted C6-C 14 -aryl, substituted or unsubstituted C7-C 18 - aralkyl, substituted or unsubstituted C1-C4-hydroxyalkyl and hydroxy;
[0158] s represents an integer from 0 to 8;
[0159] Ra and Rb are independently selected from hydrogen, substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted aralkyl, substituted or unsubstituted alkaryl, and substituted or unsubstituted aryl or heteroaryl;
[0160] (b) at least one polymeric polyanion, wherein at least 75 mol % of the monomer units of the polymeric polyanion are functionalized with functional groups selected from sulfonic acids or salts thereof, phosphonic acids or salts thereof, phosphates or salts thereof, sulfates or salts thereof and carboxylic acids or salts thereof,
[0161] Characterized in that the weight ratio of the monomer according to formula I to the monomer according to formula II is 75 / 25 to 25 / 75, preferably 70 / 30 to 40 / 60, more preferably 65 / 35 to 50 / 50.
[0162] Preferred substrates are plastics, such as polycarbonate, polyethylene, polyethylene terephthalate (PET), polyamide and polypropylene.
[0163] Prior to application of the liquid formulation, for example in the case of PET and polyolefins, a surface activation such as corona treatment may be performed to enhance adhesion to the substrate.
[0164] The substrate may also be a glass plate.
[0165] The conductive layer is preferably characterized by at least one of the following properties, more preferably all of these properties:
[0166] - Sheet resistance in 1x10 2 Up to 1x10 10 Ω / sq range, preferably 1x10 3 Up to 1x10 9 In the range of Ω / sq;
[0167] - a transmission of at least 98%, preferably at least 98.5%, more preferably at least 99%, and most preferably at least 99.5%;
[0168] - A pencil hardness of at least 6H, preferably at least 7H, more preferably at least 8H and most preferably at least 9H.
[0169] The layered bodies according to the invention are suitable for use as electronic components, in particular as conductive or antistatic devices, as transparent heaters or as electrodes.
[0170] The layered bodies can be used as electronic components, for example in films, packaging for electronic components, for finishing plastic films and for coating screens. They can also be used as transparent electrodes, for example in displays, for example as a replacement for indium tin oxide electrodes, or as electrical conductors in polymer electronics. Other possible uses are sensors, batteries, solar cells, electrochromic windows (smart windows) and displays and corrosion protection.
[0171] Considering the UV stability and scratch resistance of the coatings obtained with the liquid formulations according to the invention, these liquid formulations are particularly useful for producing antistatic coatings or electromagnetic radiation shielding. They are also particularly suitable for preparing hole transport layers in organic light emitting diodes (OLED) or organic photovoltaic (OPV) elements.
[0172] Method for preparing layered body
[0173] The method for preparing the layered body comprises the following steps:
[0174] i) providing a substrate;
[0175] ii) applying a liquid formulation according to the invention;
[0176] iii) at least partially removing the solvent from the liquid composition to obtain a layered body comprising the conductive layer coated on the substrate.
[0177] In step i), a substrate is first provided, wherein the nature of the substrate depends on the intended purpose of using the composition according to the invention. In step ii), the liquid composition according to the invention is applied to the substrate. The application of the liquid preparation can be carried out by known methods, for example by spin coating, dipping, pouring, dripping, spraying, spraying, scraping, brushing or printing, for example by inkjet printing, screen printing, gravure printing, offset printing or pad printing.
[0178] In step iii), the solvent is at least partially removed to obtain a layered body comprising a conductive layer coated on a substrate. The removal is preferably performed by drying the substrate coated with the composition at a temperature in the range of 20°C to 200°C.
[0179] Example
[0180] Material
[0181] Unless otherwise specified, all materials used in the following examples are readily available from standard sources, such as ALDRICH CHEMICAL Co. (Belgium) and ACROS (Belgium). The water used was deionized water.
[0182] EDOT is 3,4-ethylenedioxythiophene, commercially available from Heraeus.
[0183] DMOT is 3,4-dimethoxythiophene, commercially available from Fluorochem Ltd.
[0184] PSS is an aqueous solution of polystyrene sulfonic acid having a Mw of 300 kDa, prepared according to the method disclosed in Houben-Weyl, Methoden der organischen Chemie, Vol. E 20, Makromolekulaire Stoffe, Teil 2 (1987), p. 1141).
[0185] MonoPlus M600 is a basic gelular anion exchange resin commercially available from Lanxess AG.
[0186] MonoPlus S 108 H is an acidic gel anion exchange resin commercially available from Lanxess AG.
[0187] method
[0188] Surface resistance measurement
[0189] The surface resistance (SER) was measured at room temperature using a two-point probe method.
[0190] Viscosity measurement
[0191] The viscosity was measured with a glass capillary viscometer.
[0192] Gel stability measurement
[0193] The gelation stability was evaluated by mixing equal amounts of organic solvent and conductive polymer dispersion and visually assessing the gelation behavior over time. The samples were stored at room temperature or at 30°C. A quantitative measure of the gelation behavior (1-5) was determined, where 1 corresponds to no observed viscosity increase and 5 corresponds to complete gelation.
[0194] Example 1: P(EDOT 0.90 :DMOT 0.10 Synthesis of PSS
[0195] An aqueous solution of PSS (297 g, 5.74 wt%) and deionized water (1288 mL) were mixed in a reaction vessel under a nitrogen stream. EDOT (6.17 g, 43.4 mmol) and DMOT (0.69 g, 4.8 mmol) were added. The reaction mixture was heated to 30 °C while stirring. Then, a solution of iron (III) sulfate (0.31 g, 0.77 mmol) in deionized water (6.4 mL) was added. Sodium persulfate (13.7 g, 57.8 mmol) was added and the reaction mixture was stirred for 6 hours. An additional amount of sodium persulfate (2.3 g, 9.6 mmol) was added to the reaction mixture and stirred for another 16 hours. The reaction mixture was heated to 40 °C with an ion exchanger (223.9 g MonoPlus M600+419.4g The reaction mixture was treated with MonoPlus S108H, filtered and washed with 2 x 120 mL of water, repeated).
[0196] The resulting viscous mixture was split in two and treated with high shear homogenization to obtain two samples (LabGaulin, a: 1 x 600 bar and b: 4 x 600 bar).The dispersion was concentrated in vacuo.
[0197] This procedure produced blue dispersions of PEDOT:PSS in water (a: 1.12 wt % and b: 1.24 wt %).
[0198] Example 2: P(EDOT 0.80 :DMOT 0.20 Synthesis of PSS
[0199] The polymerization was carried out in the same manner as in Example 1, except that 5.49 g of EDOT and 1.37 of DMOT were used. MonoPlus M600+418.8g The reaction mixture was treated with MonoPlus S 108 H, filtered and washed with 2 x 120 mL water, repeated).
[0200] This procedure produced blue dispersions of PEDOT:PSS in water (a: 1.12 wt % and b: 1.24 wt %).
[0201] Example 3: P(EDOT 0.65 :DMOT 0.35 Synthesis of PSS
[0202] The polymerization was carried out in the same manner as in Example 1, except that 298.66 of poly(4-vinylbenzenesulfonic acid), 4.46 g of EDOT and 2.4 of DMOT were used. MonoPlus M600+417.9g The reaction mixture was treated with MonoPlus S 108 H, filtered and washed with 2 x 120 mL water, repeated).
[0203] This procedure produced blue dispersions of PEDOT:PSS in water (a: 1.23 wt % and b: 1.12 wt %).
[0204] Example 4: P(EDOT 0.50 :DMOT 0.50 Synthesis of PSS
[0205] The polymerization was carried out in the same manner as in Example 3, except that 3.43 g of EDOT and 3.43 of DMOT were used. MonoPlus M600+417.0g The reaction mixture was treated with MonoPlus S 108 H, filtered and washed with 2 x 120 mL water, repeated).
[0206] This procedure produced blue dispersions of PEDOT:PSS in water (a: 1.21 wt % and b: 1.33 wt %).
[0207] Comparative Example 1: Polymerization of PEDOT:PSS
[0208] An aqueous solution of PSS (73.2 g, 5.85 wt%) and deionized water (323 mL) were mixed in a reaction vessel under a nitrogen stream. EDOT (1.71 g, 12.1 mmol) was added. The reaction mixture was heated to 30 °C while stirring. Then, a solution of iron (III) sulfate (0.077 g, 0.19 mmol) in deionized water (1.6 mL) was added. Sodium persulfate (3.45 g, 14.5 mmol) was added and the reaction mixture was stirred for 6 hours. An additional amount of sodium persulfate (0.57 g, 2.42 mmol) was added to the reaction mixture and stirred for another 16 hours. The reaction mixture was heated to 40 °C with an ion exchanger (56.1 g, 1.6 mL). MonoPlus M600+105.1g The reaction mixture was treated with MonoPlus S 108H, filtered and repeated).
[0209] The resulting viscous mixture was treated with high shear homogenization (Lab Gaulin, 1 x 600 bar).The dispersion was concentrated in vacuo.
[0210] This procedure produced a blue dispersion of PEDOT:PSS in water (1.14 wt %).
[0211] Comparative Example 2: Polymerization of PEDOT:PSS
[0212] An aqueous solution of PSS (347 g, 5.86 wt%) and deionized water (1525 mL) were mixed in a reaction vessel under nitrogen bubbling. EDOT (8.14 g, 57.3 mmol) was added. The reaction mixture was heated to 30 °C while stirring. Then, a solution of iron (III) sulfate (0.37 g, 0.93 mmol) in deionized water (20 mL) was added. Sodium persulfate (16.4 g, 68.8 mmol) was added and the reaction mixture was stirred for 6 hours. An additional amount of sodium persulfate (2.7 g, 11.3 mmol) was added to the reaction mixture and stirred for another 16 hours. The reaction mixture was heated to 40 °C with an ion exchanger (150 g). MonoPlus M600+280g 1 L of the reaction mixture was treated with MonoPlusS 108H, filtered, and repeated).
[0213] The resulting viscous mixture was treated with high shear homogenization (Lab Gaulin, 4 x 600 bar).The dispersion was concentrated in vacuo.
[0214] This procedure produced a blue dispersion of PEDOT:PSS in water (1.22 wt %).
[0215] Example 5
[0216] The viscosity of the dispersions and the SER of rod-coated films of these dispersions on PET were measured as described above and are shown in Table 2.
[0217] Table 2
[0218]
[0219] It is clear from the results in Table 2 that the SERs of the films prepared with dispersions having increasing amounts of DMOT are comparable.
[0220] The viscosity of the dispersion decreases with increasing amounts of DMOT and enhanced homogenization.
[0221] Example 6
[0222] The gel stability of the dispersions upon addition of isopropanol was evaluated over time. The results are shown in Table 3 for storage at room temperature and in Table 4 for storage at 30°C.
[0223] Table 3
[0224]
[0225] Table 4
[0226]
[0227]
[0228] It is clear from the results in Tables 3 and 4 that dispersions containing copolymers with increasing amounts of DMOT show improved gel stability to isopropanol addition.
[0229] Example 7
[0230] The gel stability of the dispersions upon addition of ethanol was evaluated over time. The results for storage at room temperature are shown in Table 5 and the results for storage at 30°C are shown in Table 6.
[0231] Table 5
[0232]
[0233] Table 6
[0234]
[0235] It is clear from the results in Tables 5 and 6 that dispersions comprising copolymers with increasing amounts of DMOT show improved gel stability towards ethanol addition.
Claims
1. Conductive polymer dispersion, comprising: (a) at least one oligothiophene or polythiophene obtained by copolymerization of at least one monomer according to formula I and at least one monomer according to formula II, in A represents a substituted or unsubstituted C1 to C5 alkylene bridge; R is selected from a linear or branched substituted or unsubstituted C1-C 18 -alkyl, substituted or unsubstituted C5-C 12 -cycloalkyl, substituted or unsubstituted C6-C 14 -aryl, substituted or unsubstituted C7-C 18 - aralkyl and hydroxyl groups; s represents an integer from 0 to 8; Ra and Rb are independently selected from hydrogen, substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted aralkyl, substituted or unsubstituted alkaryl, and substituted or unsubstituted aryl or heteroaryl; (b) a polymeric polyanion, wherein at least 75 mol % of the monomer units of the polymeric polyanion comprise functional groups selected from sulfonic acid or salts thereof, phosphonic acid or salts thereof, phosphate or salts thereof, sulfate or salts thereof and carboxylic acid or salts thereof, (c) a dispersion medium selected from water, a water-soluble organic solvent or a mixture thereof, Characterized in that the weight ratio of the monomer according to formula I to the monomer according to formula II is 25 / 75 to 75 / 25.
2. The conductive polymer dispersion according to claim 1, wherein the weight ratio of the monomer according to formula I to the monomer according to formula II is 50 / 50 to 65 / 35.
3. Conductive polymer dispersion according to claim 1 or 2, wherein the monomer according to formula I is 3,4-ethylenedioxythiophene.
4. The conductive polymer dispersion according to any one of the preceding claims, wherein the monomer according to formula II is 3,4-dimethoxythiophene.
5. A conductive polymer dispersion according to any one of the preceding claims, wherein the polymeric polyanion is poly(4-styrenesulfonic acid) or a salt thereof.
6. Conductive polymer dispersion according to any of the preceding claims, wherein the weight average molecular weight (Mw) of the polymeric polyanion is from 50,000 to 500,000 Da.
7. The conductive polymer dispersion according to claim 1, wherein the oligothiophene or polythiophene and the polyanion are present as polythiophene / polyanion particles having a median particle size (d 50 ) is 5 to 100 nm, measured by laser diffraction.
8. Conductive polymer dispersion according to claim 7, wherein the amount of oligothiophene or polythiophene / polyanion particles is 1.1 to 1.3 wt. % relative to the total weight of the dispersion, and wherein the viscosity of the dispersion is 5 to 100 mPa.s at 20°C for 100 s. -1 Shear rate measurement.
9. A liquid formulation comprising a conductive polymer dispersion according to any one of the preceding claims.
10. Liquid formulation according to claim 9, comprising between 2 and 50% by weight of at least one organic solvent relative to the total weight of the formulation.
11. The liquid preparation according to claim 10, wherein the organic solvent is selected from methanol, ethanol, n-propanol, isopropanol, n-butanol or a combination thereof.
12. The liquid formulation according to any one of claims 9 to 11, further comprising an acid, a base, a high boiling point solvent, an adhesion promoter, a cross-linking agent, a surfactant, a binder or a combination thereof.
13. Use of a liquid formulation according to any one of claims 9 to 12 for the preparation of an antistatic coating or an electromagnetic radiation shield or for the preparation of a hole transport layer in an organic light emitting diode (OLED) or an organic photovoltaic (OPV) element.
14. A method for preparing a layered body, comprising the following steps: (i) providing a substrate; (ii) applying a liquid formulation according to any one of claims 9 to 12 to a substrate; (iii) at least partially removing the solvent from the liquid formulation to obtain a layered body comprising the conductive layer on the substrate.
15. A layered body comprising a conductive layer provided on a substrate, the conductive layer comprising: (a) at least one oligothiophene or polythiophene obtained by copolymerization of at least one monomer according to formula I and at least one monomer according to formula II, in A represents a substituted or unsubstituted C1 to C5 alkylene bridge; R is selected from a linear or branched substituted or unsubstituted C1-C 18 -alkyl, substituted or unsubstituted C5-C 12 -cycloalkyl, substituted or unsubstituted C6-C 14 -aryl, substituted or unsubstituted C7-C 18 - aralkyl and hydroxyl groups; s represents an integer from 0 to 8; Ra and Rb are independently selected from hydrogen, substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted aralkyl, substituted or unsubstituted alkaryl, and substituted or unsubstituted aryl or heteroaryl; (b) a polymeric polyanion, wherein at least 75 mol % of the monomer units of the polymeric polyanion comprise functional groups selected from sulfonic acid or salts thereof, phosphonic acid or salts thereof, phosphate or salts thereof, sulfate or salts thereof and carboxylic acid or salts thereof, Characterized in that the weight ratio of the monomer according to formula I to the monomer according to formula II is 25 / 75 to 75 / 25.
Citation Information
Patent Citations
Copolymer and composition to be used therefor
JP2012255049A
Electrolytic material formulation, electrolytic material polymer formed therefrom and use thereof
US9036333B2
Conductive polymer composite and preparation and use thereof
US9613757B2
Electrolytic capacitor and method for producing same
WO2021172199A1
